Cognitive Impairment in Neuromyelitis Optica Spectrum Disorders: A Review of Clinical and Neuroradiological Features - Oertel, Frederike Cosima; Schließeit, Jana; Brandt, Alexander U.; Paul, Friedemann (Frontiers in Neurology, 2019)
Neuromyelitis optica spectrum disorders (NMOSD) are relapsing autoimmune inflammatory disorders of the central nervous system with optic neuritis, myelitis and brainstem syndromes as clinical hallmarks. With a reported prevalence of up to 70%, cognitive impairment is frequent, but often unrecognized and an insufficiently treated burden of the disease. The most common cognitive dysfunctions are decline in attention and memory performance. Magnetic resonance imaging can be used to access structural correlates of neuropsychological disorders. Cognitive impairment is not only a highly underestimated symptom in patients with NMOSD, but potentially also a clinical correlate of attack-independent changes in NMOSD, which are currently under debate. This article reviews cognitive impairment in NMOSD and discusses associations between structural changes of the central nervous system and cognitive deficits.